Comprehending non-native speakers: theory and evidence for adjustment in manner of processing - Lev-Ari, Shiri (Frontiers in Psychology, 2015)
Non-native speakers have lower linguistic competence than native speakers, which renders their language less reliable in conveying their intentions. We suggest that expectations of lower competence lead listeners to adapt their manner of processing when they listen to non-native speakers. We propose that listeners use cognitive resources to adjust by increasing their reliance on top-down processes and extracting less information from the language of the non-native speaker. An eye-tracking study supports our proposal by showing that when following instructions by a non-native speaker, listeners make more contextually-induced interpretations. Those with relatively high working memory also increase their reliance on context to anticipate the speaker’s upcoming reference, and are less likely to notice lexical errors in the non-native speech, indicating that they take less information from the speaker’s language. These results contribute to our understanding of the flexibility in language processing and have implications for interactions between native and non-native speakers.